Limited Evidence for Parallel Molecular Adaptations Associated with the Subterranean Niche in Mammals: A Comparative Study of Three Superorders. (20th August 2018) - Davies, Kalina T J; Bennett, Nigel C; Faulkes, Chris G; Rossiter, Stephen J
Abstract: Among mammals, several lineages have independently adapted to a subterranean niche and possess similar phenotypic traits for burrowing (e.g., cylindrical bodies, short limbs, and absent pinnae). Previous research on mole-rats has revealed molecular adaptations for coping with reduced oxygen, elevated carbon dioxide, and the absence of light. In contrast, almost nothing is known regarding molecular adaptations in other subterranean lineages (e.g., true moles and golden moles). Therefore, the extent to which the recurrent phenotypic adaptations of divergent subterranean taxa have arisen via parallel routes of molecular evolution remains untested. To address these issues, we analyzed ∼8, 000 loci in 15 representative subterranean taxa of four independent transitions to an underground niche for signatures of positive selection and convergent amino acid substitutions. Complementary analyses were performed in nonsubterranean "control" taxa to assess the biological significance of results. We found comparable numbers of positively selected genes in each of the four subterranean groups; however, correspondence in terms of gene identity between gene sets was low. Furthermore, we did not detect evidence of more convergent amino acids among subterranean species pairs compared with levels found between nonsubterranean controls. Comparisons with nonsubterranean taxa also revealed loci either under positive selection or with convergent substitutions, with similar functional enrichment (e.g., cell adhesion, immune response, and coagulation). Given the limited indication that positive selection and convergence occurred in the same loci, we conclude that selection may have acted on different loci across subterranean mammal lineages to produce similar phenotypes.